Effect of Computerized Maintenance Management System on a Cement Production Plant - Adetunji, Olayide Razak; Owolabi, Samuel M; Adesusi, Olanrewaju Moses; Dairo, Olawale U; Ipadeola, Samuel O; Taiwo, Stella O (International Journal of Integrated Engineering, 2018)
This study evaluated effect of Computerized Maintenance Management System (CMMS) on a cement production plant. The materials used included a Computer and Networking system and maintenance software. Preliminary study of plant assets was carried out to identify critical plant assets and key performance indicators such as Plant Reliability Factor (RF), Number of Stoppage for Incidents (NSI) and Production Losses (PL) in 2013. The CMMS software implementation in 2015 used the data obtained. The result obtained from this implementation showed that the RF (%) for Limestone Crusher (LC), Cement Mill (CM) and Kiln were 46, 76, 86; 51, 79, 88; 59, 88, 92 in 2013, 2014 and 2015 respectively. The corresponding NSI for the three plants were 824, 472, 82; 788, 462, 56; 431, 420, 46 in 2013, 2014 and 2015 respectively. The Production Losses for the whole plant were $22.54m, $21.587m and $19.365m in 2013, 2014 and 2015 respectively.